(untitled) (JURNAL ADMINISTRASI PUBLIK, 2020)
This research aims to find out how the implementation of the policy of market retribution in Puni market of Manggarai district. This research uses qualitative method involving 6 informant that consists of the responsibility of the local levy, implementing market retribution policy and traders in the market, Manggarai district. Data collection is done by interview, observation and documentation. The results showed that the implementation of the policy of market retribution in Puni market of Manggarai district, explained that the implementation of the policy on market retribution was in accordance with the prevailing rules and regulations. The importance of this policy is deemed to conform to the interests of the target group. There are only a few obstacles that make this policy goal still difficult to achieve. One of the most dominant problems of the findings in this study is the lack of public awareness about the benefits and importance of retribution. Therefore, it takes more effort from the implementing authorities to address these issues so that policy objectives can be achieved. Key Words: Implementation of Policy, Market Retribution, Trader.